2020
DOI: 10.1007/s00066-020-01723-8
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahypofractionation of localized prostate cancer

Abstract: Due to its low fractionation sensitivity, also known as “alpha/beta ratio,” in relation to its surrounding organs at risk, prostate cancer is predestined for hypofractionated radiation schedules assuming an increased therapeutic ratio compared to normofractionated regimens. While moderate hypofractionation (2.2–4 Gy) has been proven to be non-inferior to normal fractionation in several large randomized trials for localized prostate cancer, level I evidence for ultrahypofractionation (>4 Gy) was lacking unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
(58 reference statements)
0
16
0
1
Order By: Relevance
“…This indicates that hypofractionated radiation (delivery of a higher dose to the prostate gland per treatment, for fewer total treatments) may improve cancer control. Thus, there has been great interest in moderate hypofractionation (generally accepted as 2.4-3.4 Gy per fraction (fx)) as well as ultrahypofractionation (generally accepted as >4-5 Gy/fx) (71,72). Modern noninferiority trials have demonstrated excellent overall outcomes in comparison to standard fractionation (Table 4) (73-76).…”
Section: Advances In Radiotherapy Techniques Treatment Deliverymentioning
confidence: 99%
“…This indicates that hypofractionated radiation (delivery of a higher dose to the prostate gland per treatment, for fewer total treatments) may improve cancer control. Thus, there has been great interest in moderate hypofractionation (generally accepted as 2.4-3.4 Gy per fraction (fx)) as well as ultrahypofractionation (generally accepted as >4-5 Gy/fx) (71,72). Modern noninferiority trials have demonstrated excellent overall outcomes in comparison to standard fractionation (Table 4) (73-76).…”
Section: Advances In Radiotherapy Techniques Treatment Deliverymentioning
confidence: 99%
“…There is increasing evidence to support the adoption of ultrahypofractionated schedules (≥4Gy/fraction) delivered with Stereotactic Body Radiation Therapy (SBRT) for the treatment of low/intermediate risk prostate cancer [1] . Geometric precision is paramount when a small margin is used to minimize irradiation of the surrounding organs at risk (OARs).…”
Section: Introductionmentioning
confidence: 99%
“…The use of SBRT in PCa has provided sufficient evidence in terms of tumor control results, quality of life reported by the patient, and low toxicity [4][5][6] to back its implementation in daily clinical practice. Moreover, the PCa working group of the German Society of Oncology (DEGRO) endorses the use of SBRT in the treatment of localized lowand intermediate-risk PCa, recommending its use in clinical trials in patients with the localized high-risk disease [7].…”
Section: Introductionmentioning
confidence: 99%